Hambatan Sosial Budaya Dalam Pembauran Masyarakat Tionghoa Dengan Masyarakat Lokal - Winarta, Frans Hendra (Pelita Harapan University, 2004)
More than twenty discriminatory laws and regulations are still in force, some of them dating from the Dutch colonial administration, many of them from early years of Soeharto s New Order government. Some of them are: 1.